Elaboração de uma cartilha como ferramenta no ensino de genética - Filgueiras, Manuella (Universidade Federal de São Carlos, 2025)
Learning genetics is not always an easy task. With so many scientific and abstract concepts, students feel like they are navigating a sea of information disconnected from their daily lives. With this in mind, this work presents the creation of an educational booklet about genetics applied to different areas of daily life: molecular diagnosis, taxonomy, and forensic genetics. The educational booklet can serve as a facilitator in understanding topics associated with those covered in high school, through clear and objective language and illustrations that bring the audience closer. For this purpose, three examples were selected that illustrate that genetics is part of our daily lives and goes beyond the four walls of the classroom. All of the examples use DNA as the main theme. Addressing molecular diagnosis, we sought to link it to the period of the pandemic, when the PCR technique was used to identify the COVID-19 virus. To draw attention to the importance of using DNA in taxonomy, the example of the TV series “The Last of Us” was used, where fungi play the main role: molecular biology can be an ally in taxonomy, by resolving ambiguities that are difficult to deal with based solely on morphological characters. Finally, to draw attention to the use of DNA in crime solving and ancestry analysis, the example of the TV series “CSI” was used, where in most episodes the killer was caught due to clues that involved searching for the suspect’s DNA in a database. These three themes were summarized in a light and representative manner in the booklet. It is hoped that this tool will serve to facilitate the understanding that studies involving DNA are present in people’s daily lives. It is hoped that access to the booklet will generate a feeling of connection with the topic of “genetics” among high school students and that this feeling would be carried into adulthood, facilitating decision-making involving genetics.
Development of a booklet as a tool in teaching genetics
Keywords: Metodologias ativas; Divulgação científica; Diagnóstico molecular; Cartilha educativa; Aprendizado de genética; Molecular diagnosis; Booklet; Scientific communication; Teaching; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM